Precontoured Quadrilateral Surface Acetabular Plate Fixation Demonstrates Increased Stability When Compared With Pelvic Reconstruction Plates: A Biomechanical Study. Issue 9 (September 2019) - Ryan, Weston; Alfonso, Nicholas A.; Baldini, Todd; Kumparatana, Pam; Reiter, Michael; Joyce, Christopher; Wei, Chen; Zhang, Yingzhe; Mauffrey, Cyril
Abstract : Objective: To compare the stability of 3 fixation strategies for a transverse acetabular fracture: a reconstruction plate with anterior and posterior column screws (group A); an infrapectineal precontoured quadrilateral surface buttress (iPQSB) plate alone (group B); and an anterior column lag-screw and iPQSB plate (group C). Methods: A transverse acetabular fracture was created in 18 synthetic hemipelvises. Six were fixed by each of the 3 methods described. Specimens underwent cyclic axial compressive loading to 1700N for 42, 000 cycles while anterior and posterior column displacements were measured, followed 4800N for 50 cycles. Displacement and stiffness data were analyzed with analysis of variance and Tukey HSD. A Cox proportional hazards regression model was used to determine survival rate. P values < 0.05 were considered significant. Results: Group C had significantly less posterior column displacement (0.16 ± 0.06 mm) compared with group B (0.38 ± 0.37 mm, P < 0.0001) and group A (0.38 ± 0.37 mm, P < 0.0001). In addition, group A had significantly more anterior column displacement (0.28 ± 0.11 mm) than group B (0.22 ± 0.14 mm, P = 0.0310) and group C (0.18 ± 0.09 mm, P = 0.0001). Group C was 10.5% stiffer than group A ( P = 0.0037). Group B had a 7.27x greater rate of failure than group C (95% confidence interval, 1.6–33.2). Discussion and Conclusion: Under anatomical loading, iPQSB plates with anterior column lag-screw fixation demonstrate increased stability in a synthetic bone transverse acetabular fracture model. Based on our data, we support additional evaluation of early weight-bearing after transverse acetabular fracture fixation in patients with healthy bone when an anterior column screw-iPQSB plate construct is used. Abstract : Supplemental Digital Content is Available in the Text.